2005
DOI: 10.1007/s10014-005-0186-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the constitutively activated RelA/NF-κB in human astrocytic tumors and the in vitro implication in the regulation of urokinase-type plasminogen activator, migration, and invasion

Abstract: Although malignant gliomas are highly invasive tumors, a characteristic that contributes to the commonly observed therapeutic failures and local disease recurrences, the molecular events that regulate invasion in these tumors remain poorly understood. Because the transcription factor RelA/NF-kappaB has been shown to regulate invasion during several cellular processes, we have examined immunohistochemically expression of the constitutively activated RelA/NF-kappaB in tissues obtained from 49 astrocytic tumors [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Data has shown that curcumin is able to suppress expression of MMP-1, MMP-3, MMP-9, and MMP-14 in GBM cell lines U87MG and U373MG via the common upstream AP-1 and MAP kinases [22, 23, 54]. Urokinase-type plasminogen activator (uPA) is a serine protease that starts a degradative cascade by converting extracellular plasminogen to plasmin and eventually degrades extracellular matrix collagen and activates other MMPs to aid in invasion [55]. Curcumin can prevent nuclear translocation of RelA/NF- κ B, which prevents upregulation of uPA [55].…”
Section: Mechanism and Preclinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Data has shown that curcumin is able to suppress expression of MMP-1, MMP-3, MMP-9, and MMP-14 in GBM cell lines U87MG and U373MG via the common upstream AP-1 and MAP kinases [22, 23, 54]. Urokinase-type plasminogen activator (uPA) is a serine protease that starts a degradative cascade by converting extracellular plasminogen to plasmin and eventually degrades extracellular matrix collagen and activates other MMPs to aid in invasion [55]. Curcumin can prevent nuclear translocation of RelA/NF- κ B, which prevents upregulation of uPA [55].…”
Section: Mechanism and Preclinical Datamentioning
confidence: 99%
“…Urokinase-type plasminogen activator (uPA) is a serine protease that starts a degradative cascade by converting extracellular plasminogen to plasmin and eventually degrades extracellular matrix collagen and activates other MMPs to aid in invasion [55]. Curcumin can prevent nuclear translocation of RelA/NF- κ B, which prevents upregulation of uPA [55]. Curcumin has also been found to dramatically reduce MMP-9 in murine glioma cell lines Tu-2449, Tu-9648, and Tu-251 [49].…”
Section: Mechanism and Preclinical Datamentioning
confidence: 99%
“…Since several studies have demonstrated that NF-κB is key in the transactivation of uPA and MMP9 (34)(35)(36), the present study investigated whether the activation of uPA and MMP9 may be attributed to NF-κB. As shown in Fig.…”
Section: Curcumin Inhibits P65 Nf-κb Dna Binding To the Upa And Mmp9 mentioning
confidence: 99%
“…Because several studies have demonstrated that NF-kB might have a central role in the transactivation of uPA and uPAR (Killeen et al, 2009;Sliva et al, 2002;Tsunoda et al, 2005), we explored whether PKD2-and/or PKD3-dependent expression and activation of uPA could be attributed to upregulation of NF-kB signaling. As shown in Fig.…”
Section: Knockdown Of Pkd2 and Pkd3 Inhibits The Migration And Invasimentioning
confidence: 99%